Scalable production of large single-layered graphenes by microwave exfoliation 'in deionized water'. (August 2018) - Kim, Hye-Rim; Lee, Sung-Hyun; Lee, Kun-Hong
Abstract: Single-layered graphenes with large sizes were produced by inserting solvent molecules between the graphene layers in graphite intercalation compounds (GICs) followed by direct microwave exfoliation 'in a solvent' to prevent re-aggregation. During the microwave exfoliation of GICs in deionized (DI) water, single-layered graphenes were produced, and their lateral sizes ranged from several micrometers to several tens of micrometers. The entire process time was less than 2 h, and toxic compounds were not used. In the case of microwave exfoliation in acetone or ethanol, graphenes with a thickness of 3–6 nm were mainly produced rather than single-layered graphenes. In addition, when the produced graphenes were directly dispersed in DI water, the dispersed state was maintained for 2 days. This method is very advantageous for industrial scale-up. Graphical abstract: Image 1